Elemental Composition of Various Mulberry Species - Yigit, D.; Akar, F.; Baydas, E.; Buyukyildiz, M. (Asian Journal of Chemistry, 2010)
A comparative study on the elemental composition of various mulberry fruits and leaves was conducted with wavelength dispersive X-ray fluorescence (WDXRF). The element compositions of P, K, Ca, Mg, Na, Al, Si, S, Cl, Cr, Fe, Mn, Sr and Zn were determined in white (Morus alba), red (Morus rubra) and black (Morus nigra) mulberry leaves and fruits. Significant differences (p < 0.05 or p < 0.01) were observed in the mineral contents of mulberry leaves and fruits, depending on the species. The concentrations of elements in white, red and black mulberry leaves were 4.60, 4.53 and 4.61 %, respectively of the total mass and the quantities of the elements were 2.13, 2.0 and 2.23 % of the total mass. Among the various macronutrients in the mulberry species, K was present in the highest quantity for fruits samples, whereas Ca was predominant in the leaves. However, another result found with this study shows that the main advantage of this method is the non-modification of original sample, both during sample preparation and in the exciting X-ray beam. Therefore, this method might easily be used in the diagnosis of the nutrient status of fruit trees.